Sme Loan Decision-Making Process: The Declining Role Of Human Capital - Ottavia, Ottavia; Chuluunbaatar, Enkhbold; Far Kung, Shiann; Luh, Ding Bang (Asian Academy of Management (AAM), 2011)
This study is intended to establish relationships among a borrower's attributes, the likelihood of loan approval, and the effect of lender's human capital in the SME loan-granting process. A conjoint analysis has been used as the main analytical tool. The results showed that: (1) a borrower's attributes are all positively related to the likelihood of loan approval on different levels, (2) officers place different weights on a borrower's attributes, and (3) human capital factors do not have significant roles in the SME loan-granting process